The People's Republic of China and global imbalances from a view of sectorial reforms - Hiro Ito; Ulrich Volz (Asian Development Bank Institute (ADBI), 2012)
This paper examines the impact of sectorial reforms on current account imbalances, with a special focus on the People's Republic of China (PRC). In particular, we investigate to what extent reforms pertaining to the financial sector, social protection, and healthcare may contribute to a rebalancing of the PRC's persistent current account imbalances. Our forecasting results suggest that reforming the financial sector would be a significant contributor to the country's rebalancing with an effect much larger than that of capital account liberalization. Strengthened provisions of social protection and publicly-funded healthcare are also found to contribute to a rebalancing of the PRC economy.
Keywords: F32; F41; 330; global imbalances; prc; current account balance; budget deficit; financial liberalization; social sector reform; Außenwirtschaftliches Gleichgewicht; Leistungsbilanz; Wirtschaftsreform; Branchenentwicklung; China